Análisis de mecanismos de identificación en sistemas RFID - Sánchez Martínez, Leonardo Daniel (Universidad Autónoma Metropolitana, 2016)
RFID is one of the most pervasive technologies nowadays. Its main attractiveness lies onthe ability of identifying objects with no contact or a direct line of sight between the participantdevices. An RFID system comprises two main components: an RFID network and a storage system.There are important research directions on each of these subjects, which together allow to improvethe performance of RFID technology. The RFID network is the core of an RFID system since inthis component resides the whole information of interest. Each object has attached an RFID tagwith a unique ID. The RFID reader is the central part of the RFID network, its main function is tomanipulate the information from the tags. Therefore, several processes are executed in an RFIDnetwork in order to manage such information. Normally, each process is related to an applicationand its requirements, causing an on-demand execution of a particular process. Moreover, theIdentification Processis always executed in an RFID network, which consists of collecting the tagIDs by means of the interaction between an RFID reader and the tags in the interest area. Inthis thesis, we call such a scenariothe centralized approach. Improving the performance of theidentification process is vital for the whole RFID system. Most of the research work has beenmade around the centralized approach for RFID networks; however, we identify in this work thatthis not only limits the execution of the identification process, but also limits the impact of thefuture mechanisms.A new architecture for RFID tag identification has arised in recent years. Such approach proposes to evolve from the original centralized approach to one that in some way groups tags indifferent coverage zones and executes the identification process in a distributed way. The main goalis to improve the identification delay of the system, and eventually the associated implementation costs.; La tecnologíaa RFID es ampliamente utilizada hoy en día. El gran atractivo de RFID es su habilidad de identificar objetos sin la necesidad de contacto o línea de visión directa entre los dispositivos participantes. Estas características, junto con su relativo bajo costo de implementación hacen de RFID una de las tecnologías de identificación automática más atractivas en la investigación y en la industria. Un sistema RFID tiene dos componentes principales: una red RFID y un sistema de almacenamiento. Cada uno de estos ha impuesto líneas de investigación que buscan mejorar el desempeño de la tecnología en general. La red RFID es el núcleo del sistema debido a que en esta reside toda la información de interés. Cada objeto en la red tiene una etiqueta RFID adjunta, que a su vez tiene un identificador único o ID. El lector es el dispositivo central de la red que se comunica con las etiquetas para manejar la información contenida en ellas. En una red RFID se pueden realizar diversos procesos de comunicación. Normalmente un proceso está relacionado a una aplicación en particular, es decir, se ejecuta a la demanda. Sin embargo, existe uno que se ejecuta en todo sistema RFID: el proceso de identificación. Este es el realizado entre lectores y etiquetas para recolectar el ID de cada una de ellas. En este sentido, todo el trabajo realizado en torno a este proceso se ha realizado bajo el enfoque centralizado, el cual no solo limita la ejecución del proceso de identificación, sino que también limita el impacto de futuros mecanismos. Una nueva arquitectura para la identificación de etiquetas ha surgido en años recientes. Esta propone cambiar el enfoque tradicional por uno que permita agrupar las etiquetas en subzonas de cobertura y ejecutar el proceso de identificación de manera distribuida.